Spontaneous electric polarization in the B-site magnetic spinel GeCu2O4. (April 2018) - Yanda, Premakumar; Ghara, Somnath; Sundaresan, A.
Abstract: We report the observation of a spontaneous electric polarization at the antiferromagnetic ordering temperature ( T N ∼ 33 K) of Cu 2+ ions in the B -site magnetic spinel GeCu2 O4, synthesized at high pressure and high temperature. This compound is known to crystallize in a tetragonal structure (space group I 41 / amd ) due to Jahn-Teller distortion of Cu 2+ ions and exhibit a collinear up-up-down-down (↑↑↓↓) antiferromagnetic spin configuration below T N . We found a clear dielectric anomaly at T N, where an electric polarization appears in the absence of applied magnetic field. The electric polarization is suppressed by applied magnetic fields, which demonstrates that the compound GeCu2 O4 is a type-II multiferroic. Highlights: GeCu2 O4 is prepared by high-pressure and high-temperature synthesis. Dielectric and pyroelectric current studies confirm multiferroic properties. GeCu2 O4 is a new type-II multiferroic.